Evaluation of clarity of the STOPP/START criteria for clinical applicability in prescribing for older people: a quality appraisal study - Corlina Johanna Alida Huibers; Wilma Knol; Bastiaan Theodoor Gerard Marie Sallevelt; Eugene van Puijenbroek; Toine Egberts; Ingeborg Wilting (BMJ Open)
Objectives Appropriate prescribing in older people continues to be challenging. Studies still report a high prevalence of inappropriate prescribing in older people. To reduce the problem of underprescribing and overprescribing in this population, explicit drug optimisation tools like Screening Tool of Older Persons’ potentially inappropriate Prescriptions/Screening Tool to Alert to Right Treatment (STOPP/START) have been developed. The aim of this study was to evaluate the clinical applicability of STOPP/START criteria in daily patient care by assessing the clarity of singular criteria.Design Quality appraisal study.Methods For each of the 114 STOPP/START criteria V.2, elements describing the action (what/how to do), condition (when to do) and explanation (why to do) were identified. Next, the clarity of these three elements was quantified on a 7-point Likert scale using tools provided by the Appraisal of Guidelines for Research and Evaluation (AGREE) Consortium.Primary and secondary outcomes The primary outcome measure was the clarity rating per element, categorised into high (>67.7%), moderate (33.3%–67.7%) or low (<33.3%). Secondary, factors that positively or negatively affected clarity most were identified. Additionally, the nature of the conditions was further classified into five descriptive components: disease, sign, symptom, laboratory finding and medication.Results STOPP recommendations had an average clarity rating of 64%, 60% and 69% for actions, conditions and explanations, respectively. The average clarity rating in START recommendations was 60% and 57% for actions and conditions, respectively. There were no statements present to substantiate the prescription of potential omissions for the 34 START criteria.Conclusions Our results show that the clarity of the STOPP/START criteria can be improved. For future development of explicit drug optimisation tools, such as STOPP/START, our findings identified facilitators (high clarity) and barriers (low clarity) that can be used to improve the clarity of clinical practice guidelines on a language level and therefore enhance clinical applicability.